Distributed control of manufacturing resources – security related issues - Mitrovic, Stefan; Dimic, Zoran; Jakovljevic, Zivana (Journal of Production Engineering, 2019)
Industry 4.0 paradigm dictates highly efficient and flexible production through introduction of reconfigurable manufacturing systems and resources characterized by modularity, interoperability, scalability and communication capabilities. Various approaches are currently researched worldwide in an effort to achieve the next level of production technologies without compromising the production itself. Considered approaches imply implementation of Cyber Physical Systems, Internet of Things and generation of manufacturing systems Digital Twins. Complex industrial control systems, which were traditionally wired and considered safe, are now becoming distributed, internet-connected, usually based on wireless communication and wide open for all kinds of malicious exploits with potentially fatal consequences. This paper presents a review of security related issues that are crucial in developing safer wireless distributed control of manufacturing resources, adept for challenges in coming times.